An idea to explore: Genotyping bull sperm to introduce basic molecular biology techniques in an animal science course. Issue 6 (30th August 2019) - De Groef, Bert; Grommen, Sylvia V. H.
Abstract: The laboratory exercise described here aims to provide a relevant context for learning basic DNA techniques in an introductory animal science course at tertiary level. In two 4‐hr laboratory sessions, students assess the suitability of bulls for inclusion in a gene‐assisted selection program for A2 β‐casein by genotyping commercial bull sperm. Sperm cells are lysed to extract the genomic DNA, and PCR with primers for the β‐casein gene is performed. Using the principle of amplification‐created restriction sites, restriction digestion with Taq I can be used to distinguish between the A1 allele and the A2 allele of the gene. Cut PCR amplicons are separated by gel electrophoresis to evaluate the genotype of each bull. Students then write a diagnostic report with accompanying letter to their fictional client, explaining the DNA test, and interpreting the results. © 2019 International Union of Biochemistry and Molecular Biology, 47(6):708–711, 2019.